"Dei skal ha for at dei prøver": Korleis tilsette på lokalplanet i kyrkja opplever biskopen sin tilsynspraksis - Sele, Asgeir (Tidsskrift for praktisk teologi, 2021)
This article develops knowledge about how employees in local church staffs in the Church of Norway experience the bishop's oversight practice and how they understand their own role in this practice. To shed light on this issue, distributed leadership is used as a research perspective along with institutional leadership. The article is based on data material from focus group interviews with employees in seven parish staffs and two dean groups in the same diocese. In sum, the study has shown that employees in local church staffs in the Church of Norway are unsure of what the bishop’s oversight is, something that seems to be about both weak structures in the interaction between the actors and poorly updated and adapted oversight tools. At the same time, the study shows that the same employees largely feel seen by both the bishop, the counselors in the bishop's office and by the deans. In this way, it may seem that it is the personal relations more than the structures that are relevant in the bishop's supervisory practice as it is in the Church of Norway today.